A quantitative assessment method for the correlation between rock mass basic quality and Protodyakonov coefficient - Ji, Zigang; Li, Jinhang; Zhang, Xuehui; Song, Zhanping (Frontiers in Earth Science, 2023)
With the implementation of the "Belt and Road" initiative, tunnel projects was designed in accordance with Russian design specifications and constructed by Chinese companies in countries along the route. Design companies and construction companies use different rock classification methods, which will increase the safety risk and cost of the tunnel. Therefore, it is necessary to study the correlation between Chinese engineering rock mass classification and Russian rock mass classification. In order to establish the correlation between rock mass basic quality (BQ) and Protodyakonov coefficient (f) for rock mass classification. Firstly, based on the equivalence principle of uniaxial compressive strength (UCS), the relationship between BQ and f containing velocoty index of rock mass (Kv) was established by comparing the relationship between f and BQ in the empirical formula of UCS. Secondly, through the equivalent principle of volumetric joint count of rock mass (Jv), we compared the empirical formula between intactness index of Kv and rock quality designation (RQD), and conducted linear regression analysis on a large amount of data.The relationship between Kv and RQD was established. Finally, the relationship between BQ and f is quantitatively expressed and a classification table corresponding to the Russian rock classification and the Chinese engineering rock classification is obtained. The method is applied to Kyrgyzstan mountain tunnels.